TEORI BELAJAR KOGNITIF GESTALT DAN IMPLIKASINYA PADA PEMBELAJARAN DI SEKOLAH DASAR - Andi Setiyawan; Wulan Fitriani; Zubaedah Nasucha; Suci Muzfirah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The success of an educator in carrying out learning one of them is influenced by the mastery factor of learning theory by the educator. Therefore an educator should need to understand and understand and have knowledge about learning theory so that later can apply it when educators carry out learning in school. The purpose of this article is to get to know and know what cognitive learning gestalt theory. After knowing the theory, the author will draw a link between the use of the theory with learning conducted at the elementary school level or madrasah ibtidaiyah. In this writing, using research methods of literature studies from various sources. The way data is collected in this authorship is carried out through a review of various books, literature, and reports related to both theories.